Sosialisasi Dan Pelatihan Wirausaha Sebagai Upaya Menumbuhkan Jiwa Kewirausahaan Pada Siswa Sekolah Dasar - Ahmad Nidhom Mahyuddin; Ririt Iriani Sri S; Mohammad Wahed (LPPM Politeknik Pratama, 2023)
With the rapid development of technology and the ease in distributing foreign workers, there are fewer and fewer jobs. These conditions encourage the importance of an entrepreneurial spirit for every Indonesian to be able to create jobs. The cultivation of an entrepreneurial spirit can be applied to school students because later students who are the next generation will later enter the world of work. Thus, before entering the world of work students need to be equipped with several skills including entrepreneurship skills. Therefore it is necessary to provide basic education about the importance of instilling an entrepreneurial spirit from an early age to students at SD Negeri Kauman 2. The method used in this service is qualitative by looking at the programs implemented. The results achieved from these activities are awareness of the importance of entrepreneurship in students, increased student creativity, inspiration for students to carry out entrepreneurial activities.